Developing and conducting classes using video tutorials - Сатыбалдиева, Алия; Раимбаева, Сауле; Абжаппарова, Айгерим (Pedagogy and Psychology, 2021)
This article discusses the issues of developing and conducting lessons using the method of video lessons. The stages of organizing video lessons during the distance learning are provided.The article discusses the video lesson itself in different ways, for example, the following three types of lessons can be distinguished:a lesson on the introduction (explanation) of new material; lessons on consolidation of knowledge, skills and abilities are provided; summarizes knowledge, skills and abilities and ends with a control lesson.Topical issues are addressed in order to create short videos on each topic so that students can review the material on their own and not wait for the teacher’s answer. There are several programs for creating video lessons. They are: Сamtasia Studio, Macromedia Flash, Screen2exe, Jing, Werbineria, Wink.It is shown that the whole process can be divided into three stages: write a video tutorial on Camtasia Recorder, editing (post-editing) is provided in the Camtasia Studio editor,the video file is encoded.